Paradigma Kualitatif dalam Klasifikasi Jenis Citra: Menggali Teori Revolusi Ilmiah Thomas Kuhn - Pernando, Yonky (Fakultas Komputer - Universitas Universal, 2024)
This research describes the impact of paradigm changes in science, especially in the context of image type classification. By paying attention to Thomas Kuhn's concept of paradigm, the research presents a review of contemporary historiography that highlights how paradigm shifts influence the way scientists see the world, introduce new instruments, and seek new places. However, as technologies like AI increasingly seep into everyday life, doubts remain, especially if the technology is perceived as unable to solve problems or provide the desired assistance. In the face of these doubts, the research proposes that the philosophy of communication science can provide in-depth theoretical insights, provide space for critical reflection on existing paradigms, and guide researchers in understanding the evolution of paradigms for image type classification methods. In addition, this research also considers the importance of image type classification in the context of AI technology. By identifying different types of imagery and their role as input to AI algorithms, this research provides a theoretical foundation for further understanding how AI technologies process and interpret visual data. Through a comprehensive literature review, this research aims to fill existing knowledge gaps and provide a strong theoretical basis to support further research in the field of image type classification and AI technology implementation.